Post-Translational Modification of Cav1.2 and its Role in Neurodegenerative Diseases - Li, Yun; Yang, Hong; He, Tianhan; Zhang, Liang; Liu, Chao (Frontiers in Pharmacology, 2022)
Cav1.2 plays an essential role in learning and memory, drug addiction, and neuronal development. Intracellular calcium homeostasis is disrupted in neurodegenerative diseases because of abnormal Cav1.2 channel activity and modification of downstream Ca2+ signaling pathways. Multiple post-translational modifications of Cav1.2 have been observed and seem to be closely related to the pathogenesis of neurodegenerative diseases. The specific molecular mechanisms by which Cav1.2 channel activity is regulated remain incompletely understood. Dihydropyridines (DHPs), which are commonly used for hypertension and myocardial ischemia, have been repurposed to treat PD and AD and show protective effects. However, further studies are needed to improve delivery strategies and drug selectivity. Better knowledge of channel modulation and more specific methods for altering Cav1.2 channel function may lead to better therapeutic strategies for neurodegenerative diseases.